Nylon Electrospun Nanofibre Water Filtration Media For Wastewater Treatment - Roslan, Nur Saidatul Akmal; Abdul Hamid, Nurfaizey; Md Isa, Mohamed Hafiz; Muhammad, Noryani; Mansor, Mohd Ridzuan; Abdul Munajat, Nurain (Institute Of Physics (IOP) Publishing Ltd., 2018)
Uncontrolled discharge of wastewater effluent has been a major concern due to the negative impact to human health and the environment. Increasingly stringent regulation has caused filter manufacturers to explore new materials to improve their products. Water filtration media using ultrafine fibres could be one of the potential solutions due to their promising characteristics. In this study, nanofibre incorporated water filtration media were produced, investigated, and characterized. A thin nylon electrospun nanofibre layer were deposited onto standard glass fibre filters and samples were collected at different electrospinning times. Suspended solid retention test was conducted using a vacuum filtration system based on BS EN 872:2005 standard. The absorbance of the feed and filtrate in terms of suspended solid and chemical oxygen demand of the water samples were also measured using a colorimeter based on Hach Method 8006 and 8000 respectively. The morphology of the filters was studied using scanning electron microscopy whilst porosity of the filtration media was inspected using mercury porosimetry. The results showed that the suspended solid and chemical oxygen demand removal capabilities of the filtration media improved significantly with the inclusion of nanofibre layer. A positive correlation was found between the performance of the filter and the amount of deposited nanofibre. It was also found that the inclusion of thin nanofibre layer had minimal effect to the overall porosity of the standard filters. Findings from this study provide a useful insight into the use of nanofibres in water filtration applications.